The happiness of pursuit : finding the quest that will bring purpose to your life - Guillebeau, Chris. (Harmony Books, 2014)
A book that challenges each of us to take control--to make our lives be about something while at the same time remaining clear-eyed about the commitment--The Happiness of Pursuit will inspire readers of every age and aspiration. It's a playbook for making your life count.